Harvest Data Processing Information System for Rice Productivity Prediction in Indramayu Regency - Farismana, Riyan; Sholihah, Debi Nabilah; Lena, Sonty (Jurnal Sistem Informasi Bisnis, 2025)
Rice plants that are processed into rice are the staple food of the Indonesian people, and the lack of rice production will have an impact on weakening national food security. Efforts that can be made are to process harvest data in national rice barn areas such as Indramayu Regency properly. So far, there are still many errors and differences in harvest data both by agencies and original data in the field. Differences in data cause inaccurate harvest data to be used as a reference for policies or to see the potential of rice in Indramayu. This study aims to build a website-based data processing information system so that it can be accessed and managed by agricultural officers in all sub-districts in Indramayu, and the agricultural service as admin, so that the data produced is accurate data and provides predictions of harvest results, and makes predictions of future harvests based on harvest data, land area and rainfall that affect the rice harvest in Indramayu using fuzzy tsukamoto. From the predictions made, there are 16 sub-districts that have the potential to experience a decrease in harvest from 31 sub-districts in Indramayu. This information system also displays harvest data and graphs based on year and sub-district in Indramayu so that the increase or decrease in harvest in previous years can be seen compared to predictions for the coming year.